Correlation between systemic inflammatory response and quality of life in patients with chronic rhinosinusitis. Issue 5 (18th January 2019) - Orb, Quinn; Pulsipher, Abigail; Smith, Kristine A.; Ashby, Shaelene; Alt, Jeremiah A.
Abstract : Background: Local sinonasal inflammation resulting from altered T‐cell immune signaling is a contributor to the pathogenesis of chronic rhinosinusitis (CRS). CRS patients experience negative impacts on quality of life (QOL) and suffer from comorbidities linked to systemic inflammation. However, systemic inflammatory profiling to evaluate the association between systemic inflammation and QOL in CRS has not been performed. Our objectives were to compare local and systemic inflammatory gene expression in patients with CRS to determine if systemic markers of inflammation associate with disease severity and disease‐specific QOL. Methods: A prospective observational study was conducted comparing 16 patients with CRS to 10 controls. Inflammatory gene expression in the anterior ethmoid tissues and peripheral blood of patients was measured using multiplex gene expression analysis and correlated to disease severity (computed tomography and nasal endoscopy) and disease‐specific QOL (22‐item Sino‐Nasal Outcome Test [SNOT‐22] and Rhinosinusitis Disability Index) using linear regression analyses. Results: Patients with CRS showed significant increases in the expression of ctla4 and jak1 in sinonasal tissue and blood ( p < 0.05), whereas the gene expression of hla‐dqa1, hla‐dqb1, and dusp4 was significantly decreased in patients with CRS compared to controls ( p < 0.05). Soluble and local ctla4 and jak1 showed a significant positive correlation with clinical markers of disease severity and disease‐specific QOL ( p < 0.05). Conclusion: Local and systemic gene expression involved in T‐cell immune signaling was found to be significantly altered in the blood and sinonasal tissues of patients with CRS compared to controls and significantly correlated to disease severity and QOL in patients with CRS.